1999
DOI: 10.1002/j.1550-8528.1999.tb00435.x
|View full text |Cite
|
Sign up to set email alerts
|

Beneficial Effects of Pharmacotherapy on Weight Loss, Depressive Symptoms, and Eating Patterns in Obese Binge Eaters and Non‐Binge Eaters

Abstract: ALGER, SHARON A . , MARGARET MALONE, JENNIFER CERULLI, STEVEN FEIN, LYN HOWARD. Beneficial effects of pharmacotherapy on weight loss, depressive symptoms, and eating patterns in obese binge eaters and non-binge eaters. Obes Res. 1999;7:469-476. Objective: The purpose of this study was to compare the impact of drug therapy on weight loss, Beck Depression Inventory (BDI) scores, and binge eating patterns (BES) between obese binge eaters and non-binge eaters. Research Methods and Procedures: 22 severe binge eater… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
21
1

Year Published

2000
2000
2010
2010

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 35 publications
3
21
1
Order By: Relevance
“…This widespread use is a major strength of the BDI in this population. Improvement in BDI scores has often been reported following weight loss after bariatric surgery [14][15][16][17][18][19], pharmacological interventions [20] and behavioural and dietary interventions [21][22][23][24][25][26]. We reported that symptoms of depression, measured using the BDI [27], improve following bariatric surgery and that this decrease in BDI depression scores is relatively stable up to 4 years after surgery [15].…”
Section: Introductionmentioning
confidence: 63%
“…This widespread use is a major strength of the BDI in this population. Improvement in BDI scores has often been reported following weight loss after bariatric surgery [14][15][16][17][18][19], pharmacological interventions [20] and behavioural and dietary interventions [21][22][23][24][25][26]. We reported that symptoms of depression, measured using the BDI [27], improve following bariatric surgery and that this decrease in BDI depression scores is relatively stable up to 4 years after surgery [15].…”
Section: Introductionmentioning
confidence: 63%
“…This medicine was also shown to have beneficial effects on symptoms of depression and plasma lipid levels in obese women [29,30]. Thus, treatment with phentermine results in various phenotypic effects, many of which are opposite to effects of aging.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the extensive use of fluoxetine for long-term treatment of depression, there have been no reports of cardiac valve lesions similar to those seen with fenfluramine and dexfenfluramine. 4,6,[20][21][22][23][24][25][26][27][28][29][30][31][32][33] Rothman et al 51 suggested that serotonergic drugs that bind to 5-HT (2B) receptors were associated with cardiac valve lesions. Fenfluramine and dexfenfluramine were among those that bound to 5-HT (2B) receptors, but fluoxetine did not.…”
Section: Discussionmentioning
confidence: 99%
“…[3][4][5][6][7][8][9] Weight losses at 1 year were approximately 15-17% of initial body weight with phen-fen [3][4][5][6][7][8][9] compared to losses of 6-10% of initial body weight with single-drug treatment using fenfluramine. [10][11][12][13][14][15][16][17][18][19] When fenfluramine and dexfenfluramine were removed from the market in September 1997 because of concerns about cardiac valve lesions, 4,6,[20][21][22][23][24][25][26][27][28][29][30][31][32][33] some physicians turned to combinations of phentermine and other serotonin-active drugs such as fluoxetine and sertraline in an attempt to reproduce the phen-fen effect. However, there are very few studies published on the efficacy of these combinations for obesity, and none have compared results with phen-fen.…”
Section: Introductionmentioning
confidence: 99%